Material mechanisms of Cu/Ni nanolaminate coatings resulting in lifetime extensions of welded joints. (15th April 2022) - Brunow, Jakob; Gries, Stella; Krekeler, Tobias; Rutner, Marcus
Abstract: Metal nanolaminate coatings are introduced as a new approach in post-weld treatment methods. A Cu/Ni nanolaminate coating is electrodeposited from a single Cu/Ni citrate bath onto a butt-welded tension-tension fatigue specimen. The nanolaminate coating consists of a Ni base layer and 160 alternating Cu and Ni layers. The specimen is tested in tension-tension fatigue with a stress range close to the yield strength of the specimen. This first study reveals surprisingly high lifetime extensions of welded joints. The tested specimens are examined using FIB/SEM and TEM. Local roughness measurements are carried out with AFM. This leads to observations on crack behavior of nanostructured Cu/Ni multilayers. The Cu layers show initial multi-crack formation, while the cracks arrest at the Cu/Ni interfaces. The Ni layers bridge those cracks and each Ni layer tears individually. Hypotheses are formed on the fatigue behaviour of Cu/Ni multilayers. Graphical abstract: Image, graphical abstract